Confessions : The Private School Murders - Patterson, James 1947-; Paetro, Maxine (New York ; Little, Brown and Company, 2013)
Teenage detective Tandy Angel attempts to exonerate her famous brother of murder charges, track down a New York City killer, and figure out what happened to her lost love.
Sequel to: Confessions of a murder suspect.